Analisis Strategi Operasional dan Pengembangan UMKM Bintang Bakery Menggunakan Pendekatan SWOT, Balanced Scorecard, dan Cost–Benefit Analysis - Siti Masyfuah Azzahro (Indo Publishing, 2025)
This study aims to analyze the operational strategy and business sustainability of the Bintang Bakery MSME in West Aceh Regency. The analytical approaches used include SWOT, Balanced Scorecard (BSC), and Cost–Benefit Analysis (CBA). Data were obtained through direct observation, interviews with the business owner, and daily operational documentation. The results indicate that Bintang Bakery's main strengths lie in product quality, customer loyalty, and consistent production processes. However, weaknesses remain, including limited production capacity and marketing that is not yet digitally integrated. The CBA indicates that the business is financially viable with an average net profit of IDR 12,500,000 per month and a Benefit–Cost Ratio (BCR) > 1. From a BSC perspective, the business has met customer and internal process indicators, but needs improvement in employee learning and asset development. This study recommends increasing production capacity, optimizing layout, using simple technology, and strengthening digital marketing strategies.